Health Belief Model and Hand Hygiene Compliance Among Nurses in the Wards of RSUD dr. H. Kumpulan Pane Tebing Tinggi - Popi Latifah Bawean; Chrismis Novalinda Ginting; Sri Wahyuni Nasution (Jurnal Ilmu Kesehatan Masyarakat, 2024)
One of the intermediaries for infection transmission between patients is through the hands of health workers. Hand hygiene is an easy, cheap, and effective precaution, but very difficult to implement. This study aims to determine the effect of health beliefs on nurse hand hygiene compliance in the inpatient ward of RSUD dr. H. Kumpulan Pane (HKP). This quantitative analytic study with a cross-sectional design was conducted at the inpatient ward of RSUD HKP. This study involved 210 inpatient ward nurses. Data collection was carried out using survey techniques, valid and reliable questionnaires, and direct observation. The majority of respondents were 36-40 years old (40.5%), were female (91.4%), had an associate degree (74.8%), had worked for 6-10 years (57.1%), and were civil servants (56.7%). All respondents had attended Infection Prevention and Control (IPC) training, experienced sharp object injuries and contact with patient body fluids, and 85.7% of respondents had experienced nosocomial infections. The majority of respondents had good perceptions of susceptibility, severity, benefits, cue to action, and self-efficacy, but the majority of respondents also had high perceptions of barriers. Further observation found that nurses' hand hygiene compliance was only around 56.7%. Data analysis found that nurses’ hand hygiene compliance at RSUD HKP was influenced by perceived susceptibility (p<0.001), severity (p<0.05), cue to action (p<0.001), and age (p<0.005). It can be concluded that although all components of the health belief model were associated with hand hygiene compliance, only perceived susceptibility, severity, cue to action, and age had a significant influence on hand hygiene compliance.